Legal Protection For Indonesian Migrant Workers From a Criminal Act of Trafficking - Kadek Merry Herawati (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Violations committed by private worker placement companies in deploying ineligible, illegal and/or non-procedural workers abroad can lead to a criminal act of Trafficking in Persons. Required procedures of Indonesian workers placement to foreign countries based on Law No. 39 of 2004 were not properly conducted, and accordingly, as prescribed in the provisions of Law No. 39 of 2004, such action is potential to be classified as criminal acts of human trafficking. Legal protection for Indonesian workers who are assigned overseas is of preventive form, that is legal protection provided starting from the pre-placement period: placement period, up to a post-placement period; and repressive legal protection, the protection granted through deliberation, but if an opportune agreement cannot be reached through deliberation, the settlement can be done through court institution.